Does SarsCoV-2 infection really cause damage to retinal microcirculation in mild cases of COVID-19? - Adisa Pilavdžić; Suzana Pavljašević; Amra Nadarević Vodenčarević; Anis Međedović; Meliha Halilbašić; Alma Čičkušić; Nejra Hodžić; Sumeja Terzić; Azra Šmigalović; Sanela Muhović (Medicinski glasnik, 2023)
Aim: To evaluate changes of retinal microcirculation in mild cases of recovered COVID-19 patients at least three months after the infection by optical coherence tomography angiography (OCTA) non-invasive method. Methods: In this prospective cross-sectional study, 50 right eyes of 50 recovered COVID-19 patients were compared with 50 right eyes of age and gender-matched healthy controls. After the complete ophthalmological examination, all participants underwent OCTA measurements (RTVue XR Avanti, Optovue, Fremont, CA, USA). Results: The time between the initial onset of symptoms, and ophthalmologic examination was 479.20 ±197.10 (126-754) days. Findings of ophthalmic examination of all eyes of the recovered COVID-19 patients were within normal range. Significantly reduced superficial (p=0.046) and deep (p=0.044) macular vessel density (VD) in foveal region in the eyes of the recovered COVID-19 patients was found compared with healthy controls. Significantly enlarged foveal avascular zone (FAZ) area and perimeter in the eyes of the recovered COVID-19 patients (p<0.001) were found too. Conclusion: Recovered COVID-19 patients have impaired retinal microcirculation, which can be a cause of the development of retinal vascular diseases.
Keywords: coronavirus; OCT angiography; retina; vascular density